Cloning and Characterization of Cellulase from Paenibacillus peoriae MK1 Isolated from Soil - Sang Jin Kim; Kyung-Chul Shin; Dae Wook Kim; Yeong-Su Kim; Chang-Su Park (Fermentation, 2023)
An isolated bacterium from soil that highly hydrolyzes cellulose was identified as Paenibacillus peoriae and named P. peoriae MK1. The cellulase from P. peoriae MK1 was cloned and expressed in Escherichia coli. The purified recombinant cellulase, a soluble protein with 13.2-fold purification and 19% final yield, displayed a specific activity of 77 U/mg for CM-cellulose and existed as a metal-independent monomer of 65 kDa. The enzyme exhibited maximum activity at pH 5.0 and 40 °C with a half-life of 9.5 h in the presence of Ca2+ ion. The highest activity was observed toward CM-cellulose as an amorphous substrate, followed by swollen cellulose, and sigmacell cellulose and α-cellulose as crystalline substrates. The enzyme and substrate concentrations for the hydrolysis of CM-cellulose were optimized to 133 U/mL and 20 g/L CM-cellulose, respectively. Under these conditions, CM-cellulose was hydrolyzed to reducing sugars composed mostly of oligosaccharides by cellulase from P. peoriae MK1 as an endo-type cellulase with a productivity of 11.1 g/L/h for 10 min. Our findings will contribute to the industrial usability of cellulase and the research for securing cellulase sources.